INISIATIF GREEN HUMAN RESOURCE MANAGEMENT TERHADAP KINERJA LINGKUNGAN PERUSAHAAN DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR FOR ENVIRONMENT DAN PROACTIVE ENVIRONMENTAL STRATEGY SEBAGAI VARIABEL INTERVENING Studi Pada Holding PT Samudera Indonesia Tbk - Irkhami, Wahyu Lazwar; Djastuti, Indi (Faculty of Economics and Business Diponegoro University, 2024)
ABSTRACT This research aims to determine and analyze the intitiative of green human resource management on firm environmental performance through organizational citizenship behavior for the environment and proactive environmental strategy as intervening variables at the holdings of PT Samudera Indonesia Tbk. The study includes the entire population of managerial-level employees under the Samudera Logistics business unit consists of 61 respondents. Data collection involved distributing questionnaires to the research sample using a hybrid approach, both directly and through electronic mail. The questionnaire measured samples using a Likert Scale (5 points), and hypothesis testing was conducted using the Structural Equation Modelling (SEM) method with the assistance of SmartPLS software version 4.0. The statistical test results indicate that the green human resource management variable does not have a significant direct influence on firm environmental performance. This was also found in testing the intervening variable of proactive environmental strategy, which did not significantly mediate the influence between the two. However, the influence between green human resource management and firm environmental performance becomes significant when mediated by the organizational citizenship behavior for the environment variable.